Financial Ratio Analysis for PT XL AXIATA Tbk - Evi Grediani (Profesional Muda Cendekia Publishing, 2021)
This study aims to determine the performance of financial statements and health level PT XL Axiata Tbk. This study also investigates based on the ratio of profitability, liquidity, activity and solvency from the 2015-2020 period. The company's soundness assessment method uses the Altman Z-Score method. The results of the study of profitability ratios indicate that the performance of financial statements is not very good because it is not optimal in generating profits. The liquidity ratio shows that the performance of the financial statements is not very good in meeting its current liabilities. The activity ratio shows that the company's financial statement performance is less effective in utilizing the asset turnover ratio and its working capital but has been maximized in collecting receivables from customers. The solvency ratio shows poor financial statement performance because the company's financial risk is very large but the company is able to pay interest expense when it matures. The results of the analysis of the Altman Z-Score method show that the company's health level is in a vulnerable state and has a high risk of bankruptcy